A study on factors that contribute to employees attitude in an organization at employees provident fund Seremban branch / Ain Masalina Aishya Shaharudin - Shaharudin, Ain Masalina Aishya (Faculty of Business and Management, 2014)
The present study aims to investigate the factors that contribute to employees’ attitude in an organization at Employees Provident Fund Seremban branch. This research studied on three variables that influence employees’ attitude which are working environment, work-life balance and compensation. The population of the studied comes from workers of Employees Provident Fund from ages in the range of 26 up to more than 40 years old with different education background, salary. Data was collected through distribution of the questionnaires to 100 staffs of Employees Provident Fund Seremban branch by using simple random sampling. Result of correlation analysis for the present study shows that there is a relationship between the independent variables and employees attitude at Employees Provident Fund Seremban branch. Researcher also have used regression backward analysis in identifying the most factor that influence employees’ attitude at Employees Provident Fund Seremban branch and the result was working environment. This study can also be used by any other organization in order to gain their competitive advantage. Recommendations for the organization also have been discussed.